DNA Barcoding sebagai Inovasi Bioteknologi untuk Identifikasi dan Konservasi Tanaman Lokal: Suatu Tinjauan Sistematis - Syahriani; Hala, Yusminah (INSTITUT AGAMA ISLAM NEGERI AMBON, 2026)
Limitations in accurate and efficient species identification techniques at various stages of development and sample conditions are major problems in the conservation of local plants. Conventional morphology-based identification approaches often encounter obstacles due to phenotypic variation and diagnostic character limitations. This study aims to examine the potential of DNA barcoding as a biotechnology innovation in supporting the identification and conservation of local plants. The research method used was a systematic literature study of national and international scientific articles published between 2020 and 2025. Data sources were obtained from the PubMed, Scopus, ScienceDirect, and Google Scholar databases, then analyzed thematically by grouping findings based on the type of genetic marker, identification procedure, and relevance to plant conservation. The results of the study show that DNA barcoding is a species identification technique carried out through the analysis of deoxyribonucleic acid sequences from specific standard marker genes. In plant taxonomy, chloroplast genes commonly used as genetic markers include ribulose bisphosphate carboxylase large chain, maturase K, and internal transcribed spacer. The genetic sequences obtained are then compared with a global database to accurately determine species suitability. This technique has been proven to provide fast and reliable species identification under various sample conditions. With these advantages, DNA barcoding has great potential as a key supporting tool in local plant conservation efforts. Keywords: DNA Barcode, Biotechnology, Plant Conservation